Limits of Corporate Social Responsibility in Global Production Networks - Naz, Farah; Boegenhold, Dieter (Journal of Arts & Social Sciences, 2022)
The article is part of an emerging South-centred critical perspective on corporate social responsibility (CSR). Despite growing academic interest in critical CSR, the existing literature is relatively silent on gendered outcomes of CSR practices. This article intends to fill this gap in the CSR literature by initiating a conversation about the dynamics of gender and CSR approaches in global supply chains with particular reference to the Global South by providing a specific institutional context of CSR for reflection. Empirically, the research focuses on a region in Pakistan where a large number of female home-based workers stitch footballs for Western brands. The findings are based on a qualitative study that unpacks the complexities of CSR in Global Production Networks (GPNs) and reflects on the unintended negative consequences that arise when gender-blind CSR approaches are uncritically envisaged and implemented in the Global South. The study reasserts the need for broader and more inclusive CSR approaches in GPNs. The authors suggest that contextualized and gendered CSR approaches are necessary to improve labour conditions in international supply chains.